2020
DOI: 10.1111/wvn.12432
|View full text |Cite
|
Sign up to set email alerts
|

Testing of the Nursing Evidence‐Based Practice Survey

Abstract: Background: Clinicians' knowledge and skills for evidence-based practice (EBP) and organizational climate are important for science-based care. There is scant literature regarding aligning organizational culture with EBP implementation and even less for unit and organizational culture. The Nursing EBP Survey examines individual, unit, and organizational factors to better understand registered nurses' (RN) self-reported EBP.Aims: Establish and confirm factor loading, reliability, and discriminant validity for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
0
19
1
2
Order By: Relevance
“…The importance of a master's degree has also been recognized in other research (Chang & Levin, 2014; Chen et al., 2020; Gallagher‐Ford et al., 2020; Kim et al., 2016; Skela‐Savič et al., 2020; Yoo et al., 2019). Contrary to previous research results (Chen et al., 2020; Crawford et al., 2020; Stokke et al., 2014; Yoo et al., 2019), access to databases was not a significant factor for reported beliefs on and implementation of EBP in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The importance of a master's degree has also been recognized in other research (Chang & Levin, 2014; Chen et al., 2020; Gallagher‐Ford et al., 2020; Kim et al., 2016; Skela‐Savič et al., 2020; Yoo et al., 2019). Contrary to previous research results (Chen et al., 2020; Crawford et al., 2020; Stokke et al., 2014; Yoo et al., 2019), access to databases was not a significant factor for reported beliefs on and implementation of EBP in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in a comparison of EBP results between nurses working in hospitals and medical offices, Crawford et al. (2020) showed that the first group received a better result compared to the second group. Conversely, our study showed that inclusion into 24‐hr hospital care is not a factor of successful EBP implementation.…”
Section: Discussionmentioning
confidence: 99%
“…We look for problems who underwent prosthetic tively seek evidence, deal with problems, and improve the quality of clinical nursing services. 14 The results of this study showed that the psychological state of patients in the study group was better than control group after intervention, and the scores of HADS-A and HADS-D in the study group were lower than control group. It is indicated the anxiety and depression score of the study group was lower than the control group, and the same as the mental health level of the study group.…”
Section: Discussionmentioning
confidence: 62%
“…At the same time, evidence‐based nursing is a nursing model established through the continuous transformation and development from traditional clinical nursing concepts to modern nursing models. It can encourage nurses to use critical thinking develop approaches, actively seek evidence, deal with problems, and improve the quality of clinical nursing services 14 . The results of this study showed that the psychological state of patients in the study group was better than control group after intervention, and the scores of HADS‐A and HADS‐D in the study group were lower than control group.…”
Section: Discussionmentioning
confidence: 78%
“…Intermountain Healthcare has over 300 nurse educators supporting over 10 000 registered nurses across the organization. The Council conducted a systemwide survey to assess baseline understanding of evidence-based practice implementation using a validated instrument 4. Based on the findings, Intermountain decided to invite faculty from the Helene Fuld Health Trust National Institute for Evidence-based Practice in Nursing and Healthcare at The Ohio State University to train interested nurses from across the enterprise.…”
Section: Education and Networkingmentioning
confidence: 99%